2009
DOI: 10.1190/1.3054145
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous spectral attributes using scales in continuous-wavelet transform

Abstract: Instantaneous spectral properties of seismic data — center frequency, root-mean-square frequency, bandwidth — often are extracted from time-frequency spectra to describe frequency-dependent rock properties. These attributes are derived using definitions from probability theory. A time-frequency spectrum can be obtained from approaches such as short-time Fourier transform (STFT) or time-frequency continuous-wavelet transform (TFCWT). TFCWT does not require preselecting a time window, which is essential in STFT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Wavelet transform, S transform and generalized S transform are the main methods used for compensation [7,8].…”
Section: ) High Frequency Compensationmentioning
confidence: 99%
“…Wavelet transform, S transform and generalized S transform are the main methods used for compensation [7,8].…”
Section: ) High Frequency Compensationmentioning
confidence: 99%
“…Reine et al (2009) found that variable-window time-frequency transforms such as continuous-wavelet transform (CWT) shows better robustness and accuracy for attenuation measurements than fixed-window transforms. Spectral decomposition from CWT has better time-frequency resolution than short-time Fourier transform (STFT), so the instantaneous spectral attributes from Wavelet transform are expected to be better than those from STFT (Sinha et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…From this wavelet transform the instantaneous frequency of every scale of the real signal is obtained. Wavelet transform provides a natural window for signals that requires high time resolution at high frequencies and high frequency resolution at low frequencies based on the dilation property of a wavelet and does not require preselecting a time window, which is essential in STFT (Sinha et al, 2009). The instantaneous attributes obtained by wavelet analysis have certain effects on the analysis of non-stationary signals such as edge detection (see, for example, Aydin et al, 1996;Schmeelk, 2005) and image compression (see, for example, Lewis and Knowles, 1992;Boix and Cantó, 2010), the time-frequency distribution in time series (see, for example, Farge, 1992), fault diagnosis (see, for example, Jena and Panigrahi, 2012) and lithological characteristics identification (see, for example, Perez-Muñoz et al, 2013) and gas detection(see, for example, Kazemeini et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bradford and Wu ͑2007͒ apply wavelet decomposition to transform GPR data in the t-f domain. Sinha et al ͑2009͒ present an alternative wavelet transform ͑WT͒, which holds real promise for geophysical data analysis. Here, we use the S-transform, which offers the resolution of WT along with an important advantage of STFT, namely, the accurate estimation of both amplitude and phase ͑Stockwell, 2007͒.…”
Section: Introductionmentioning
confidence: 99%